1970
DOI: 10.4319/lo.1970.15.4.0522
|View full text |Cite
|
Sign up to set email alerts
|

Foraminiferal Populations and Marine Marsh Processes1

Abstract: Low marsh and high marsh foraminifera1 populations are related to mean tide levels in some places. This information can be used to estimate tidal regime, current velocities, and water exchange in a coastal lagoon containing marshes if area and bathymetry of the lagoon are known, The least diverse faunas have agglutinated tests and occur in high runoff areas in tropical, temperate, and subarctic areas studied. The most diverse faunas contain abundant calcareous lagoon and open-ocean spccics and result from inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0
6

Year Published

1978
1978
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 8 publications
1
35
0
6
Order By: Relevance
“…Coles, 1977;Coles and Funnell, 1981;Boomer, 1998;Funnell and Boomer, 1998;Haslett et al, 1997;Horton et al, 1999;Gehrels et al 2001;Horton and Edwards, 2005, in press), Europe (e.g. Phleger, 1970;Pujos, 1976;le Campion, 1970;Murray, 1991;Gehrels and Newman, 2004) and North America (e.g. Scott, 1976;Scott andMedioli, 1978, 1980a, b;Patterson, 1990;Gehrels, 1994, 1999, Spencer, 2000Guilbault et al, 1996;Hippensteel et al, 2000Hippensteel et al, , 2002Gehrels et al, 2000Gehrels et al, , 2002Martin et al, 2003;Edwards et al, 2004a, b;Patterson et al, 2004;Culver and Horton, 2005;Tobin et al, 2005; Horton and Culver, in press;), and tropical mangroves (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Coles, 1977;Coles and Funnell, 1981;Boomer, 1998;Funnell and Boomer, 1998;Haslett et al, 1997;Horton et al, 1999;Gehrels et al 2001;Horton and Edwards, 2005, in press), Europe (e.g. Phleger, 1970;Pujos, 1976;le Campion, 1970;Murray, 1991;Gehrels and Newman, 2004) and North America (e.g. Scott, 1976;Scott andMedioli, 1978, 1980a, b;Patterson, 1990;Gehrels, 1994, 1999, Spencer, 2000Guilbault et al, 1996;Hippensteel et al, 2000Hippensteel et al, , 2002Gehrels et al, 2000Gehrels et al, , 2002Martin et al, 2003;Edwards et al, 2004a, b;Patterson et al, 2004;Culver and Horton, 2005;Tobin et al, 2005; Horton and Culver, in press;), and tropical mangroves (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It is dominated by numerous calcareous species such as H. germanica, A. beccarii, E. williamsoni and Quinqueloculina spp. Similar studies from Europe also identified tidal flat faunal zones dominated by calcareous species (Phelger, 1970;Pujos, 1976;Coles, 1977;Coles and Funnell, 1981;Murray, 1991;Boomer, 1998;Funnell and Boomer, 1998). However, most studies from North America have not identified low marsh and tidal flat fau-nal zones because most taxa found in the middle and lower marshes extend into the tidal flat area (Scott and Medioli, 1980a;Williams, 1989;Patterson, 1990;Scott and Leckie, 1990).…”
Section: Intertidal Foraminiferal Zonationmentioning
confidence: 69%
“…Previous contemporary foraminiferal investigations have largely been carried out on the Atlantic Medioli, 1978, 1980a;Smith et al, 1984;Gehrels, 1994a,b;De Rijk, 1995a,b;De Rijk and Troelstra, 1997) and the Pacific coasts of North America (Williams, 1989;Patterson, 1990;Jennings and Nelson, 1992;Guilbault et al, 1995Guilbault et al, , 1996Jennings et al, 1995;Scott et al, 1996), and the Atlantic seaboard of Europe (Le Campion, 1970;Phelger, 1970;Pujos, 1976;Murray, 1991). Those that exist from the UK (Coles, 1977;Coles and Funnell, 1981;Boomer, 1998;Funnell and Boomer, 1998) are somewhat ambiguous as the altitudes were not levelled to an absolute elevation.…”
Section: Intertidal Foraminiferal Zonationmentioning
confidence: 99%
See 1 more Smart Citation
“…Un gran número de trabajos han estudiado la distribución de los foraminíferos modernos en las marismas salobres del Atlántico Norte (e.g., Le Campion 1970, Phleger 1970, Pujos 1976, Scott & Medioli 1978, 1980a, Smith et al 1984, Murray 1991, Gehrels 1994a, 1994b, De Rijk 1995, De Rijk & Troelstra 1997, Cearreta et al 2002, Moreno et al 2005, Woodroffe et al 2005, Horton & Edwards 2006, Fatela et al 2007, Horton & Edwards 2006, Horton & Murray 2007, Horton & Culver 2008, Leorri et al 2008, del Atlántico Sur (e.g., Cusminski et al 2009) y del Pacífico Norte (e.g., Williams 1989, Patterson 1990, Jennings & Nelson 1992, Guilbault et al 1995, 1996, Scott et al 1996, lo que en algunos casos ha permitido la posterior aplicación de la "función de transferencia".…”
unclassified